New doors open for organic synthesis: total synthesis of (±)-Aspidophyline A - Medina, Juan Pablo (2011)
Organic synthesis has gone through many changes over the past few years, new concepts and reactions have been incorporated into the tools available for the synthesis. In 2011 the synthesis of Aspidophylline A, an alkaloid furoindoline, was reported. This synthesisis of great importance because it validates the interrupted Fischer indolization.